The development of hybrid binder using cassava starch-epoxy resin blends - Nur Adibah Mohd (2017)
This research studies the development of hybrid binder by using two different types of binder which are cassava starch and epoxy resin. The cassava starch and epoxy resins were blended to produce a hybrid binder which is more environmental friendly, cassava starch was chosen because of good ductility, good adhesion, self-curing and hygroscopicity resistance while epoxy resin has high elastic modulus, low creep, low density, strong bond ability, good electrical insulation properties, chemical resistance, convenient manufacturing process and good performance at elevated temperature. The aims of this study were to prepare the hybrid binder based on epoxy resin with different concentration of cassava starch, to characterize the functional group of hybrid binder and to evaluate the effect of cassava starch concentration in hybrid binder on the tensile, impact and bending test. FTIR result shows the spectral patterns of all samples are approximately similar. Mechanical properties were tested by using tensile, impact and bending test. The hybrid binder with 20% of cassava starch exhibited better mechanical properties than others except for tensile test which is 80% cassava starch has maximum elongation.